2001
DOI: 10.1007/s003830100008
|View full text |Cite
|
Sign up to set email alerts
|

Typhoid ileal perforation in Nigerian children: an analysis of 106 operative cases

Abstract: Typhoid ileal perforation (TP) is a major problem in developing countries and carries a high mortality. The purpose of this retrospective study from Nigeria was to review the outcome in children less than 15 years of age who underwent surgery for TP from 1984 to 1999. Demographic data, clinical features, results of investigations, findings at surgery, postoperative course, and complications were recorded. There were 55 boys and 51 girls. The median age at presentation was 10 years (range 3-14). The surgically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
77
3
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(88 citation statements)
references
References 0 publications
5
77
3
3
Order By: Relevance
“…[5] The prognosis of typhoid ileal perforation is still poor despite several years of treating it in our societies, with mortality rates ranging from 10% to 25% in children. [5,6] In this study, case fatality for TP was 12.5% and this was as a result of overwhelming sepsis, postoperative continuing peritonitis, wound infection and wound dehiscence. [7] It was noted that mortality among children with multiple perforations (4 or more) stood at 28%.…”
Section: Discussionmentioning
confidence: 84%
“…[5] The prognosis of typhoid ileal perforation is still poor despite several years of treating it in our societies, with mortality rates ranging from 10% to 25% in children. [5,6] In this study, case fatality for TP was 12.5% and this was as a result of overwhelming sepsis, postoperative continuing peritonitis, wound infection and wound dehiscence. [7] It was noted that mortality among children with multiple perforations (4 or more) stood at 28%.…”
Section: Discussionmentioning
confidence: 84%
“…Similarly, it has also been suggested that infection with multi-drug resistant (MDR: resistant to ampicillin, chloramphenicol, trimethoprim / sulfamethoxazole) S. Typhi may impact clinical severity and outcome although little is known about MDR S. Typhi infection in young children 13 . However, isolation of the organism takes at least 48-72 hours and the yields is often very low at 40-75%, hence limiting its use to a confirmatory basis only 14 . Widal test has become the most commonly used serologic test in the diagnosis of typhoid fever in endemic areas of the developing world where bacteriologic facilities are lacking 15 .…”
Section: Resultsmentioning
confidence: 99%
“…8 The incidence of typhoid related intestinal perforation is an indication of endemicity of typhoid fever in any locality. 2,9 Enteric perforation is more common in people of lower socio-economic status.This is probably related, poor hygiene and limited access to healthcare facilities.…”
Section: Discussionmentioning
confidence: 99%
“…1 In developing countries, typhoid fever still remains a major health problem because of poor sanitary conditions. 2 Among the various complications the most lethal are intestinal bleeding and ileal perforations, both arising from hyperplasia and necrosis of Peyer's patches in the terminal ileum usually occurring 2-3 weeks after the onset of the disease. 1,3 Although intestinal hemorrhage is the most common complication of typhoid fever, intestinal perforation is the complication associated with highest morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%